THE ARTISTIC REPRESENTATION OF SOCIAL INEQUALITY IN ENGLISH AND UZBEK LITERATURE: (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Relevance of the study. Social inequality remains one of the most urgent and enduring problems of human society, and its reflection in literature has always played a crucial role in raising social awareness. Literary works often serve as a mirror of social reality, revealing injustice, class division, poverty, and moral conflict. In this context, the novels of Charles Dickens and Abdulla Qodiriy occupy a significant place, as both writers realistically portray the lives of people affected by unequal social conditions.